2022
DOI: 10.3390/vaccines10101647
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo-like Lesions and COVID-19: Case Report and Review of Vaccination- and Infection-Associated Vitiligo

Abstract: Several cutaneous manifestations in patients undergoing COVID-19 vaccination have been described in the literature. Herein, we presented a case of new-onset vitiligo that occurred after the second dose of the Comirnaty vaccine. An updated literature search revealed the occurrence of a total of 16 cases, including new-onset or worsening of preexisting vitiligo. Given the autoimmune pathogenesis of the disease, we reviewed and discussed the potential role of the vaccine prophylaxis as a trigger for the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, they found that the mean age of COVID-19 patients with vitiligo was significantly lower than those without vitiligo [ 19 ]. This finding is consistent with other studies that have reported a higher prevalence of COVID-19 in younger patients with vitiligo [ 20 ]. The duration of vitiligo appearance is also an important factor that has been studied in relation to COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, they found that the mean age of COVID-19 patients with vitiligo was significantly lower than those without vitiligo [ 19 ]. This finding is consistent with other studies that have reported a higher prevalence of COVID-19 in younger patients with vitiligo [ 20 ]. The duration of vitiligo appearance is also an important factor that has been studied in relation to COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Laura Macca et al reviewed 16 cases of vitiligo after COVID‐19 infection and COVID‐19 vaccination reported in the literature. They realized that the symptoms of vitiligo usually appear within 1 week after vaccine administration 6 . Our patient had received the COVID‐19 vaccine 6 and 4 months before the initiation of vitiligo and the depigmented lesions appeared on the second day of receiving RDV during SARS‐CoV‐2 infection, therefore, it can be said that vaccine is unlikely to have caused the disease.…”
Section: Discussionmentioning
confidence: 81%
“…Vitiligo is an autoimmune skin disease affecting approximately 0.5%–2% of the world population and can be accompanied by other autoimmune diseases 6,7 . It is a multifactorial disorder comprising genetics and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate and adaptive immune responses are involved in the pathogenesis of vitiligo, with T cell subsets playing a central role, cytotoxic CD8+ T cells mediating melanocyte clearance, regulatory T cells (Treg) maintaining immune homeostasis and suppressing infammation, and skin-resident memory T cells (TRM) inducing vitiligo recurrence. Keratinocytes exacerbate the disease by secreting chemokines to recruit more cytotoxic CD8+ T cells [13,14].…”
Section: Discussionmentioning
confidence: 99%